IDENTIFIKASI GARIS PANTAI DI PROVINSI LAMPUNG YANG RAWAN OLEH TSUNAMI SEBAGAI AKIBAT LETUSAN GUNUNG KRAKATAU - Dwi Jokowinarno (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
Identification of Lampung Province coastline that vulnerable of Krakatau Volcano explosioninduced tsunami is a part of natural disaster mitigation. Krakatau is a volcanic island that lay onSunda Strait. During 26th to 28th of August 1883, this volcano exploded with a giant explosionequal to 200 Megaton TNT that caused some of islands disappeared and 35,500 of casualties.Tsunami has celerity much greater than wind induced waves. In the deepwater condition, wavescelerity is in order of magnitude 43 km hour-1, while tsunami celerity could reach 700 km hour-1.Lampung Province main island coastlines have various distances (40km to 121km) to the sourceof Krakatau Volcano explosion. The level of vulnerability depends on the distances of location tosource of explosion, and availability of shore protection included geomorphology. The level ofrisk area is a combination of the level of vulnerability and the degree of importance from thesocial, politic, economic, and strategic defense point of view. Teluk Betung coastal zone, Panjang,and Kota Agung coastline respectively is the highest risk due to this area has the most importantfrom the social, politic and economic point of view, although has further distance compare toMount of Rajabasa Region.